Методи за оценка на перформансите на монетарната политика со посебен осврт на Република Македонија - Георгиевска, Љупка (Економски факултет, УКИМ, Скопје, 2013)
This PhD study aims to provide an independent and critical evaluation of monetary policymaking in the Republic of Macedonia in historical terms, thus representing, to the best of our knowledge, the very first study of this type. Based on recommendations from the economic literature and following the contemporary central banks’ “best practices”, the evaluation covers four aspects of monetary policy making: 1) assessment of central bank’s performance against its mandate; 2) evaluation of the quality of the macroeconomic projections as important input in the monetary policy decision-making process; 3) assessment of monetary policy credibility and 4) assessment of central bank’s transparency and communication. We apply consistent methodological framework incorporating core principles and commonly used practices for good monetary policy evaluation. Our methodological approach is extensively discussed in separate part of the study. In addition we elaborate on most popular monetary policy strategies – monetary targeting, exchange rate targeting and inflation targeting – touching upon their basic characteristics as well as the inherent advantages, disadvantages and constraints of every each of them. In the study we also offer an overview of monetary policy goals, capacity and constraints, thus defining the limits of monetary policy – what it can and can not do – as a starting point in every monetary policy evaluation.
Methods for Monetary Policy Evaluation and the Case of the Republic of Macedonia
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубе Трпески.
Keywords: monetary policy, evaluation, Republic of Macedonia